Developmental Ecological Psychology: Changes in Organism-Environment Systems Over Time, Part I. Issue 1 (2nd January 2018) - Read, Catherine; Szokolszky, Agnes
ABSTRACT: This article introduces the first part of a 2-part Special Issue of Ecological Psychology dedicated to the enhancement of developmental ecological research and theory and to finding common ground with broader ecologically relationally oriented developmental science. The Special Issue has been motivated by the observation that Developmental Ecological Psychology is a still emerging core discipline that has much to offer both to Ecological Psychology and to other ecological-dynamical-relational approaches in developmental science. This introduction briefly reviews the 4 articles in the first part of the Special Issue and urges further theoretical and empirical work in the framework of Developmental Ecological Psychology. We emphasize that an Ecological Psychology that does not include developmental theory and research over the life span and across species is not a complete Ecological Psychology.